Menigkatkan Pertumbuhan dan Produksi Bawang Merah (Allium ascolanicum L) pada Media Gambut dengan Pupuk Kompos Serasah Jagung dan Frekuensi NPK 16:16:16 - M. Nur; Selvia Sutriana (Seminar Nasional Lahan Suboptimal, 2018)
Nue et al, 2019. Increasing Growth and Production of Onion (Allium ascolanicum L) in Peat Media with Corn Litter Compost Fertilizer and NPK Frequency 16:16:16. pp. 110-119.Sumatra's widest peatland in Riau Province, but development of Horticultural crops, one of which is onion, has not been utilized to the maximum, is due to the nutrient-poor and acidic peatlands. The use of compost and correct frequency of NPK fertilization can improve the nature of the peatland and increase crop yields. the study was to determine the effect of interaction and the growth and production of onion in media with the addition of corn litter compost and the frequency of NPK 16:16:16. The study was conducted at the Experimental Garden of the Faculty of Agriculture, Universitas Islam Riau from April to August 2018. Completely randomized design study used, the first factor was corn litter compost 10, 20 and 30 tons / ha, the second factor was NPK fertilization frequency 16:16:16 namely 1 and 2 times the fertilization dose of 150, 300 and 450 kg / ha. Parameters observed were plant height, number of leaves, age of tuber formation, age of harvest, weight of tubers per tuber, production per hectare. The results show that there is a significant interaction effect on tuber weight per tuber and production per hectare with the best treatment of compost 30 tons / ha and 2 times fertilization dose 150 kg / ha per once (300 kg / ha). The main effect is real compost fertilizer on tuber weight per tuber and production per hectare, with the best treatment of 30 tons / ha and the main effect of real fertilization frequency on tuber weight per tuber, with the best treatment 2 times of 150 kg / ha per once (300 kg / ha).